Performance analysis of a Savonius hydrokinetic turbine having twisted blades. (August 2017) - Kumar, Anuj; Saini, R.P.
Abstract: In the quest for renewable energy sources, kinetic energy available in small water streams, river streams or human-made canals may provide new avenue which can be harnessed by using hydrokinetic turbines. Savonius hydrokinetic turbine is vertical axis turbine having drag based rotor and suitable for a lower flow velocity of the water stream. In order to enhance the efficiency of the turbine, this paper aims to analyze the performance of twisted blade Savonius hydrokinetic turbine. Using CFD analysis, an attempt has been made to optimize blade twist angle of Savonius hydrokinetic turbine. The simulation of a twisted Savonius hydrokinetic turbine having two blades has been carried out to investigate the performance. Commercial unsteady Reynolds-Averaged Navier-Stokes (URANS) solver in conjunction with realizable k-ε turbulence model has been used for numerical analysis. Fluid flow distributions around the rotor have been analyzed and discussed. It has been found that Savonius hydrokinetic turbine having a twist angle of 12.5° yields a maximum coefficient of power as 0.39 corresponding to a TSR value of 0.9 for a given water velocity of 2 m/s. Highlights: Savonius rotor having twist angle ranging from 0° to 25° is proposed. CFD study is carried out for water velocity varied from 0.5 m/s to 2 m/s. Flow distribution around the Savonius hydrokinetic turbine is discussed. Effect of twist angle and Reynolds number on performance of rotor was studied.